Indonesia is a tropical country that has high variety of mangrove. Of 15.9 thousand ha world mangrove forest total area, the 3.7 thousand ha, or 24% of it is located in Indonesia. The aims of the research are: 1) to identify both the potential and the types of utilization of mangrove ecosystem carried out by the local society; 2) to analyze the economic value of the mangrove ecosystem; and (3) to analyze the alternatives of strategic utilization for mangrove ecosystem .. The number of respondent - Moch Prihatna Sobari; Luky Adrianto; Nurdiana Azis (Buletin Ekonomi Perikanan, 2006)
Indonesia is a tropical country that has high variety of mangrove. Of 15.9 thousand ha world mangrove forest total area, the 3.7 thousand ha, or 24% of it is located in Indonesia. The aims of the research are: 1) to identify both the potential and the types of utilization of mangrove ecosystem carried out by the local society; 2) to analyze the economic value of the mangrove ecosystem; and (3) to analyze the alternatives of strategic utilization for mangrove ecosystem .. The number of respondents is 138 deriving from Fishery Household (RTP) and non-RTP. The data were then analyzed by using consumer surplus, household model, Total Economic Value (TEV), and Multi Criteria AnalysiS (MCA). The results show that the biggest utility is the one of crabs that reaches Rp19, 770,799.11, with the surplus consumer of Rp17,664,744,08. The highest optimum profit from the crab utilization amountsto Rp12,883,900.00 for 11 (eleven) fishery households; while the lowest profit is obtained from the utilization of prawn pond with Rp3,165,590.70. The biggest proportion is from the indirect utilization' with a percentage of 83.71% with a value of Rp1,039,474,428.00 per year. Furthermore, the Total Economic Value of the mangrove forest ecosystem in 8arru District covering 6.23 ha of mangrove forest and 127.60 ha for ponds amounts to Rp1,241 ,763,891.75. The utilization altematives put as priorities, based on the balance between indicators for both efficiency criteria and ecology criteria, between the efficiency and equity criteria, not only in the level of real interest rate of 4.·12% but also at the real interest rate of 3.55% are as follows: firstly, utilization alternative V (100% mangrove forest and 0% ponds); secondly, utilization altemative IV (8.73 ha mangrove forest and 0 ha shrimp monoculture pond, 104.05 ha mallet monoculture pond, and 21.00 ha poly-culture). Nevertheless, the utilization alternative III, II, and I cannot be given as choices in this management since their analysis values show that they are not efficient.